Pengembangan Media Pembelajaran Monopoli Ciri-Ciri Mahluk Hidup Di Madrasah Ibtidaiyah Kanigoro Blitar - Puji Asmaul Chusna; M. Jamil Hadi Wijaya (Program Studi Pendidikan Agama Islam, 2021)
This study aims to see the feasibility of developing learning media used to solve problems in the thematic learning process for the characteristics of living things to be more effective, interesting and fun. By using the Research and Development (R&D) method, the researcher developed a game-based learning media based on the Borg and Gall procedure using only 4 stages of development that adopted the monopoly game. Through the results of 3 validators, namely material experts at 80.5%, media design experts at 95%, and learning experts at 90%, this research shows that the validation is at a very valid qualification percentage, so this monopoly game-based learning media is very feasible to use. used. This is also evidenced by the results of large-scale pre-test and post-test field trials with 83.6% results.